Repetition in Mandarin Chinese: An Exploration of Functions, Types, and Interactional Function - Huiya Zhu (Journal of Linguistics and Communication Studies, 2025)
Repetition is a common feature in everyday spoken discourse and serves various communicative functions beyond simple reiteration. This study categorizes repetition into two main types based on its position in a turn: (1) repetition at the beginning of a turn, which combines with other elements to form a complete turn, and (2) repetition forming an independent turn, where the repeated content stands alone. The study employs conversation analysis (CA) to examine naturally occurring data from telephone conversations between family members, friends, and some institutional talk. Through a bottom-up approach, the study explores the dual functions of repetition in conversation. The findings reveal that repetition serves several social and communicative functions, including linking turns, initiating corrections, expressing attitudes or emotions, and seeking explanations. For example, repetition at the beginning of a turn often facilitates the smooth continuation of a conversation, while repetition in an independent turn can initiate a correction or invite clarification. Additionally, repetition can signal the speaker’s stance or emotional response to prior content, influencing the course of the interaction. This study highlights the complexity of repetition as a conversational tool and emphasizes the importance of context in interpreting its function. The research suggests that future studies should further investigate the diverse roles of repetition in communication, requiring comprehensive corpus data for deeper analysis.